REMOVED: PB 16 Restingstate alterations under antidepressant treatment and the relation to sexual side effects – comparison of bupropion, paroxetine and placebo. Issue 10 (October 2017) - Metzger, C.; Abler, B.; Grön, G.; Walter, M.; Graf, H.
Abstract : This article has been removed: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been removed at the request of the Publisher, as the authors did not give permission for the abstract to be published.